Solitary Giant Intramuscular Myxoid Neurofibroma Resulting in an above Elbow Amputation - Gururajaparasad Chennakeshaviah; Sunila Ravishankar; Rangaswamy Maggad; G. V. Manjunath (Hindawi Limited, 2012)
Neurofibromas are uncommon benign tumours and are still rarer in intramuscular locations. They are not detected until they cause a significant damage to the neighbouring tissues. We present a case of a giant intramuscular myxoid neurofibroma of the left forearm which eroded the radius and ulna, restricting the movements at the elbow and wrist joints and causing wrist drop resulting in an above elbow amputation. It was diagnosed by histopathology and was later confirmed by immunohistochemistry.